Utilization of Social Media in Government Transformation in the Digital Era - Alya Fauziah; Kamal Nugraha; Davina Fitri Nuraini; Luthfiyah Ramadhani; Dimas Eka Pratama Maulana (GoResearch - Research & Publishing House, 2024)
Digital transformation in governance has become a global trend that disrupts various aspects of life, includinggovernment management. Social media has emerged as a crucial innovation tool in this transformation,enabling direct interaction between the government and the public, as well as the rapid and widespreaddissemination of information. This study aims to explore how social media is utilized to support governmenttransformation in the digital era. We employed a literature review method to analyze and synthesizeinformation from various credible sources. Our findings indicate that social media plays a significant role inenhancing transparency, public participation, and communication between the government and society.Additionally, social media can be used as a tool to improve the efficiency and effectiveness of governmentservices. However, this research also identifies several challenges associated with the use of social media ingovernance, such as the risk of misinformation, data misuse, and ineffective communication management.Therefore, appropriate strategies are needed to optimize the use of social media as an integral part of digitaltransformation in governance. By understanding the role of social media in this context, it is hoped that morestrategic and effective models for utilizing social media can be developed to enhance government performanceand strengthen relationships with the public. This study also aims to contribute to the development of theoriesand practices related to digital transformation in governance.